Parenting children with ADHD : 10 lessons that medicine cannot teach - Monastra, Vincent J. (APA Lifetools, 2014)
In this second edition, Dr. Vince Monastra provides practical, step-by-step guidance to parents looking for ways to bring out the best in kids with attention-deficit/hyperactivity disorder. He presents updated lessons about the causes of ADHD, how medications work, and the problems that sleep deficits, poor nutrition, and other medical disorders can cause. He also shares his innovative approach for improving organization, task completion, problem solving, and emotional control.